Soviet sea fisheries since the Second World War - Armstrong, Terence (Polar Record, 1966)
A number of recent publications in English (Borgstrom, 1961; Herman, 1964; Helin, 1964; Kravanja, 1964; Shparlinskiy, 1964) have dealt with aspects of the growth of Soviet fisheries since the Second World War. Some of these publications are written from inside the Soviet fishing industry, others by western fisheries specialists. There would be no advantage in covering the same ground again in detail. The object of this paper is to draw attention to certain features of the Soviet industry not very fully considered in the accounts just mentioned. Before this can be done, however, it will be necessary to sketch in, as background, enough indication of the growth to make the rest of the paper comprehensible.